Enhanced Antimalarial Activity of Extracts of Artemisia annua L. Achieved with Aqueous Solutions of Salicylate Salts and Ionic Liquids - Ferreira, Ana M (2024)
© 2024 The Authors. Co-published by Zhejiang University and American Chemical Society.